Path Analysis on the Effect of Stress, Sleep Quality, and Hypertension on Type 2 Diabetes Mellitus Incidence in the 30-60 years Age Group in Medan City - Riri Oktavani Banjarnahor; Fazidah Aguslina Siregar; Asfriyati Asfriyati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Non-communicable diseases are still the leading cause of death worldwide, affecting not only the elderly but also the productive age group. Type 2 diabetes mellitus (DM) is one of the non-communicable diseases whose prevalence continues to rise, including in Indonesia. North Sumatra Province also experienced an increase in DM prevalence, with the highest number of cases in Medan City. The development of type 2 DM is a complex process and is associated with several risk factors, one of which is psychological stress. This study aims to analyze the effect of stress on the incidence of type 2 DM in the 30-60 years age group in Medan City directly and indirectly through sleep quality and hypertension. The research method used a case control design with a sample size of 68 cases and controls each. Data analysis was carried out univariately and multivariately using a path analysis model. The results showed that there is a direct effect between stress (b=0.892; 95% CI=0.149-1.636; p=0.019) on the incidence of type 2 DM in the 30 -60 years age group in Medan City. Stress increases the risk of type 2 DM indirectly through poor sleep quality (b=0.886; 95% CI=0.188-1.583; p=0.013) and hypertension (b=0.859; 95% CI=0.117-1.602; p= 0.023). In addition, sleep quality (b=0.820; 95% CI=0.076-1.565; p=0.031) and hypertension (b=1.046; 95% CI=0.249-1.841; p=0.010) also have a direct effect on type 2 DM. Avoiding and managing stress, getting enough and regular sleep, and controlling blood pressure can help prevent type 2 DM.Keyword: Hypertension, Sleep Quality, Stress, Type 2 Diabetes Mellitus